A thermo-viscoplastic constitutive law for isotropic hardening of metals - Schindler, Stefan; Steinmann, Paul; Aurich, Jan C.; Zimmermann, Marco (Archive of Applied Mechanics, 2016)
A novel empirical constitutive law for thermo-viscoplasticity is proposed, which considers isotropic strain and strain rate hardening as well as thermal softening. The yield stress considers strain rate and thermal effects independently for the initial yield stress and the (strain) hardening stress. To date, most plasticity models consider strain rate and temperature effects only combined for the initial and hardening stress, which is not sufficient for several materials. Seidt and Gilat (Int J Solids Struct 50(2):1781–1790, 2013) presented comprehensive experimental measurements for the aluminum alloy Al2024 including isothermal compression tests at low strain rates and various constant temperatures from room temperature to almost melting temperature as well as adiabatic compression tests at high strain rates (up to 10,900 s-1). In contrast to established thermo-viscoplastic material models, the proposed model is suitable to describe the material behavior of Al2024 accurately over a large range of loading conditions, i.e. from small to large plastic strains, low and high strain rates, and from room temperature to melting temperature, which is validated by the experimental data of Seidt and Gilat (2013). Consequently, with the use of the proposed constitutive law a variety of applications can be modeled, e.g. bulk forming, hot working, chip formation during cutting processes, or crash simulations. It is in particular promising for applications where combined loading conditions occur, like high strain rates and high temperatures at the chip formation.
Keywords: Strain hardening; Strain rate hardening; Thermal softening; Al2024